Structural and defects induced phenomena in γ-rays irradiated 6H-SiC. (October 2016) - Sibuyi, P.; Ngom, B.D.; Kotsedi, L.; Izerrouken, M.; Madjoe, R.; Maaza,
Abstract: Damages and/or defects induced by γ-rays irradiation on 6H-SiC single crystals in channeled configuration towards 〈006〉/〈0012〉 crystallographic directions are reported in the range of 0–1200 kGy. Atomic force microscopy, X-rays diffraction, Raman and photoluminescence investigations were used to obtain a comprehensive set of informations on the nature and population distribution of the induced defects. Primarily, there was no carbon clusterization upon γ-rays irradiation and hence no formation of others SiC polytypes. In contrast, the γ-rays irradiation has induced an increase of the surface roughness at higher doses, which indicates a structural degradation. Larger doses induced an emergence of deeper shallow traps at energies greater than 350 meV below the bandgap. Highlights: No formation of others SiC polytypes. The gamma rays irradiation has induced a slight surface amorphization. A re-crystallization at lower and higher doses is noticed. Larger doses induced a substantial internal stress.